2009
DOI: 10.1002/cmdc.200800447
|View full text |Cite
|
Sign up to set email alerts
|

Derivation of a Retinoid X Receptor Scaffold from Peroxisome Proliferator‐Activated Receptor γ Ligand 1‐Di(1H‐indol‐3‐yl)methyl‐4‐trifluoromethylbenzene

Abstract: Abstract1-Di(1H-indol-3-yl)methyl-4-trifluoromethylbenzene (DIM-Ph-4-CF 3 ) is reported to inhibit cancer cell growth and to act as a transcriptional agonist of peroxisome proliferator-activated receptor γ (PPARγ) and nuclear receptor 4A subfamily member 1 (NR4A1). In addition, DIMPh-4-CF 3 exerts anticancer effects independent of these receptors because PPARγ antagonists do not block its inhibition of cell growth, and the small pocket in the NR4A1 crystal structure suggests no ligand can bind. Because PPARγ a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 69 publications
0
6
0
Order By: Relevance
“…They have been shown to regulate Nur77 function by modulating Nur77-dependent transactivation, influencing its expression levels, inducing nuclear export of Nur77 or affecting binding to other proteins ( 80 88 ). Many of these compounds have, as also shown for 6-MP, also Nur77-independent actions ( 85 , 89 , 90 ). In cancer cells, neuronal cells, as well as different immune cells, it has been shown that Nur77 function depends on tissue context, subcellular localization, external stimuli, protein–protein interactions, or post-translational modifications ( 22 26 , 31 , 32 , 34 , 35 , 37 , 38 , 60 ).…”
Section: Discussionmentioning
confidence: 53%
“…They have been shown to regulate Nur77 function by modulating Nur77-dependent transactivation, influencing its expression levels, inducing nuclear export of Nur77 or affecting binding to other proteins ( 80 88 ). Many of these compounds have, as also shown for 6-MP, also Nur77-independent actions ( 85 , 89 , 90 ). In cancer cells, neuronal cells, as well as different immune cells, it has been shown that Nur77 function depends on tissue context, subcellular localization, external stimuli, protein–protein interactions, or post-translational modifications ( 22 26 , 31 , 32 , 34 , 35 , 37 , 38 , 60 ).…”
Section: Discussionmentioning
confidence: 53%
“…29 was synthesized as described for 1 , but the final cyclocondensation was conducted with (1-isopropyl-1 H -indol-3-yl)oxoacetic acid methyl ester, which was synthesized from 1-isopropyl-1 H -indole as described . ES-MS: 481 [M + H] + .…”
Section: Methodsmentioning
confidence: 99%
“…25 Hz, 1H), 8.12 (s, 1H), 11.2À11.4 (br, 1H), 11.9À12.2 (br, 1H). 13 3-(7-Chloro-1H-indol-3-yl)-4-[2-(4-methylpiperazin-1-yl)quinazolin-4-yl]pyrrole-2,5-dione (26). 26 was synthesized as described for 1, but the final cyclocondensation was conducted with commercially available (7- 3-(1-Isopropyl-1H-indol-3-yl)-4-[2-(4-methylpiperazin-1-yl)quinazolin-4-yl]pyrrole-2,5-dione (29).…”
Section: -(3-chloroisoquinolinmentioning
confidence: 99%
“…The synthetic Nur77 agonists 1,1-di(3-indolyl)-1-(p-substituted-phenyl)methanes (DIM-arenes) have been shown to affect Nur77 activation in a structure-dependent manner. Interestingly, DIM-arenes also act as transcriptional agonists for PPARγ and RXRα (22), suggesting that they are not specific agonists for Nur77. We recently found that the natural product cytosporone B (Csn-B), an Nur77 agonist isolated from Dothiorella sp.…”
Section: Introductionmentioning
confidence: 99%